Techno-nationalism/-globalism/-socialism over information and communication technology (ICT): The International Political Economy of U.S.-China Technological Hegemony and EU's Social Shaping - Takahiro Kawamata (International Telecommunications Society (ITS), 2023)
The struggle for technological supremacy between the U.S. and China that has emerged over the 5G mobile network has spread to various aspects of the international community, ranging from issues of national security to the protection of personal information. Originally, information and communication technology were closely related to national military technology, and it can be said that the development of this technological field has changed the form of warfare in the past world wars and in the postwar Cold War structure. Today, this field is being extended to include not only outer space but also cyberspace as a new area of conflict. On the other hand, in the economic realm as well, real space is becoming more integrated with virtual space, and as virtual space is swallowing up real space, VR, AR, and the world of the metaverse are becoming more expansive. This struggle for hegemony over the information and communication technology (ICT) domain is transcending national frameworks and revealing a structure in which global markets incorporate local climates, creating geopolitical and economic conflicts of principles and values. Bloomer (2021) describes a geopolitical situation in which big tech companies are emerging as players in the U.S.-China conflict and the world order, where "globalism" (Apple, Google, Facebook) and "nationalism" (Amazon, Microsoft / Alibaba, ByteDance, Huawei) and "techno-utopianism" (Tesra). In addition to these players, however, suppliers of digital products, services, and information flows to build information and telecommunications infrastructures include Ericsson and Nokia in Europe, Samsung in Korea, Huawei in China, and the semiconductor industry supply chain in Taiwan, as well as in Europe, the United States, Japan, and China. The supply chain of Taiwan's semiconductor industry, along with those of Europe, the U.S., Japan, and China, is also influencing technonationalism. This paper analyzes and discusses the balance of power among nations over technological hegemony in the industrial ecology and geopolitical economics power structure issues of information and communication technology using an international political economy approach.
Keywords: 330; Technological Hegemony; International Political Economy; Structural Powers; "Big Tech (Platformers)"; GPT (General Purpose Technology); "Technosocialism"